Examining Franz Brentano's Concepts of Good and Bad in Sophocles' Antigone: Insights for Islamic Moral Consideration - Bita Iraji (UIN Raden Mas Said Surakarta, 2024)
The purpose of this research is to investigate the good and bad themes of love and recognition in Sophocles' Antigone, which is within the framework of Franz Brentano's philosophical concepts and Islamic views. The main questions asked are: How do love and recognition help to understand good and bad actions in the narrative of